The Domination Industrial Agriculture and the New Rurality - Morett Sánchez, Jesús Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
At present some of the traditional differences between rural and urban areas are becoming less clear and there is a school of thought called new rurality, to describe the changes in agrarian societies with expanding nonfarm multiactivity farmers and in cities and even the so-called peri-urban agriculture. Currently between rural and urban elderly interconnections exist in the past, resulting in the gear between intensification and, in some parts (mainly in developed countries) some cities become more “rural” (home gardens) and the field is “urbanized” for access to metropolitan services (drainage, electricity, telephone, etc.) and the facility in rural industries and local services previously nonexistent. The links between the two sectors have intensified and become more complex, which is expressed in the diversification of activities and relationships that were not previously had, all this within the context of greater integration into the international market. Relations between the two sectors have intensified and become more complex, which is expressed in the diversification of activities and relationships that did not exist, all the above within the context of greater integration into the international market. It is necessary to be clear within the new landscape re-articulation and contradictory relationship between agriculture and industry, since the rural-urban contradiction remains, on the contrary, becomes more complex.